KAJIAN DIGITALISASI PELABUHAN TERHADAP KINERJA LOGISTIK AGROINDUSTRI DI PROPINSI LAMPUNG - Taufik Rahman; Feti Arman (Journal of Management and Industrial Engineering (JMIE), 2022)
The study in this article is the digitization of ports in supporting agro-industrial logistics in Lampung Province. In writing this article, the research method used is the study of literature and secondary sources through a qualitative approach. Multi-modal transportation means that logistics in Lampung Province involves more than one type or mode of transportation. Data from the Ministry of Industry noted that Indonesia's logistics costs reached 24 percent of GDP. High logistics costs make Indonesia's Logistic Performance Index (LPI) rank low, at 46 in 2018. Indonesia is still losing to Malaysia at 41, Vietnam at 39, Thailand at 32, and Singapore at 7. Utilizing information technology, logistics can be accomplished. So it is hoped that with digitization, the delivery time of agro-industrial products and the costs incurred will be more efficient. The conclusion obtained is that the long waiting time experienced by agro-industry entrepreneurs when shipping goods through the port to the destination area can be reduced, one of which is through digitizing the port by utilizing information technology. Through port digitization, it is hoped that it will reduce dwell time and realize logistics connectivity through the development of multimodal logistics access (land and sea).